Effect of Vitamins B12 and D Deficiency in Thyroid, Skin, Oral, and Respiratory Disease - Praveen K. Tagore; Prashant Harit; Manish K. Sachan; Mahendra K. Bharti; Pratima Singh; Gauri Harit (Journal of Pharmacy and Bioallied Sciences)
Background: Vitamin B12 and vitamin D play crucial roles in maintaining metabolic and immune homeostasis. Deficiencies in these vitamins have been linked to multiple systemic and localized disorders, including thyroid dysfunction, dermatological conditions, oral pathologies, and respiratory diseases. Materials and Methods: A cross-sectional study was conducted on 200 participants aged 20–50 years, divided into two groups: individuals with vitamins B12 and D deficiencies (n = 100) and healthy controls (n = 100). Serum vitamin B12 and vitamin D levels were assessed using chemiluminescent microparticle immunoassay (CMIA). Thyroid function tests (TSH, T3, and T4), dermatological assessments, oral health indices (DMFT index, oral mucosal examination), and pulmonary function tests (spirometry) were recorded. Statistical analysis was performed using SPSS software, with a significance level set at P < 0.05. Results: Vitamins B12 and D deficiencies were significantly associated with hypothyroidism (P = 0.003), increased prevalence of skin conditions such as eczema and psoriasis (P = 0.021), higher incidence of recurrent aphthous stomatitis and burning mouth syndrome (P = 0.017), and impaired pulmonary function with reduced FEV1/FVC ratio (P = 0.038). Mean vitamin B12 levels in the deficient group were 180 ± 45 pg/mL, while mean vitamin D levels were 12.4 ± 3.7 ng/mL. Conclusion: Deficiencies in vitamins B12 and D contribute to multiple systemic disorders, affecting thyroid function, skin integrity, oral health, and respiratory function. Early detection and supplementation may help mitigate these adverse effects.